Comparative study of anaesthesia induction in obese dogs using propofol dosages based on lean body weight or total body weight. (December 2020) - Devito, Fernanda Corrêa; Patricio, Geni Cristina Fonseca; Flôr, Patrícia Bonifácio; Vendramini, Thiago Henrique Annibale; Amaral, Andressa Rodrigues; Pfrimer, Karina; Brunetto, Marcio Antonio; Cortopassi, Silvia Renata Gaido
Abstract: The objective of this study was to compare the dosages for anesthesia induction in obese dogs using propofol based on lean body weight or total body weight. For this purpose, seven dogs with ideal body condition score (BCS) (BCS 4-5; 17.3 ± 2.5% fat mass) were included in the control group (CG), seven obese dogs (BCS 8-9; 45.7 ± 2.9% fat mass) in the total body weight group (TBWG) and seven obese dogs (BCS 8-9; 42.8 ± 6.3% fat mass) in the lean body weight group (LBWG). Anaesthesia was induced by a constant rate infusion of propofol at 150 mg kg −1 hour −1 through a propofol infusion pump until the loss of consciousness; the animals in CG and TBWG received a propofol infusion based on total body weight; the animals in LBWG received a propofol infusion based on lean body mass (in kg) determined by the deuterium dilution method. The results were compared between the groups using the Tukey test ( p < 0.05). The propofol dosage used was 11.4 ± 3.2 mg kg −1, 8.0± 2.0 mg kg −1 and 14.1 ± 4.7 mg kg −1 in groups CG, TBWG and LBWG, respectively, and they were different among all groups ( p < 0.001). There was also a statistical difference in the time between the start of propofol infusion and loss of consciousness in which LBWG took longer than CG and TBWG ( p  = 0.004). This study shows that obese dogs require lower dosages of propofol when inducing anesthesia than ideal BCS dogs anesthetized with dosages based on total body weight, when the propofol dosages are calculated on the basis of muscle mass it should be increased.